(untitled) (Medicine Today, 2017)
Clubfoot is the commonest congenital deformity in babies. Around 80% of the cases occur in developing nations. There are many options for treating club foot, Ponseti technique is one of them. This observational study was carried out at Chittagong Medical College Hospital, From July 2014 to December 2015 to evaluate the results of idiopathic club foot / feet within 1 year of age by Ponseti technique. Patients with idiopathic congenital club foot (CTEV) is attended at the outpatient department of CMCH. Among the 35 patients, 1 patients 2.85% required 1 plaster, 2 patients (5.74%) required 2 plaster, 3 patients (8.57%) required 4 plaster, 5 patients (4.28%) required 5 plaster, 16 patients (45.71%) required 6 plaster, 5 patients (14.28%) required 7 plaster cast and 3 patients (8.57%) required 8 plaster cast with or without percutaneous tonotomy. The final score after completion of the management (with or without tenotomy) were 0 of 39 feet (75%) which were normal and 0.5 of 10 feet (19.24%) and score 1 of only 3 feet (5.76%) which were better than moderately abnormal. Medicine Today 2017 Vol.29(2): 42-45